Hypoxic Status Is Associated With The Intensity Of Hypoxia Inducible Factor (Hif)-1α Expression In A Premature Placenta - Kartini Edwin (Universitas Muhammadiyah Malang, 2021)
Prematurity refers to live births before 37 weeks of gestation and associated with infant morbidity/mortality. Activation of HIF during the final pregnancy phase is believed to play a critical role in the pathogenesis of premature birth and other pregnancy disorders. This study aimed to analyze the relationship between hypoxicstatus and the intensity of HIF-1α expression in a premature placenta.Stored biological materials premature placenta (paraffin blocks) was used in this study. Thirtyone samples of placental hypoxia (H) and 28 samples of premature placental non-hypoxia (N) as controls, were selected non-random consecutively. Subsequently, immunohistochemistry was performed to analyze HIF-1α expression. TheChi-square testwas used to analyze the data and a p-value <0.05 was considered statistically significant.Moderate to strong intensity of HIF-1α expressionwas observed in 58% of hypoxic placenta samples, whereas most of non-hypoxic placental samples(86%) did not expressed or expressed weaklyHIF-1α.There was a significant correlation between the intensity of HIF-1α expression and placental hypoxia (p <0.05) and Odds Ratio (OR) value was 8.31 with a 95% confidence interval (2.32-29.77). The conclusion shows that hypoxic status is associated with intensity of hypoxia inducible factor (HIF)-1α expression in a premature placenta.